Evaluation of fatigue strength of cruciform welded joints by strain energy density method based on singular strength factor. (August 2020) - Shen, Wei; Zuo, Mou; Xu, Shuangxi; Liu, Enqian
Highlights: A simple notch stress assessment formula based on singular strength factor was presented. Evaluation accuracy of strain energy density by the simplified formula was analyzed. The W - N evaluation curve was proposed and verified with the simplified formula. Abstract: In order to simplify the fatigue assessment method of the notch stress intensity factors (N-SIFs) and the strain energy density (SED) approach for cruciform welded joints, a simplified notch stress assessment formula was presented based on singular intensity factors a s i . It is worth emphasizing that the proposed simple formula is only determined by the distribution of notch stress field and is independent on the peak notch stress. Meanwhile, singular intensity factors a s i are in one-to-one correspondence with N-SIFs and SED parameters, thus avoiding the establishment of a very refined mesh model. On this basis, the evaluation accuracy of SED by the traditional numerical method and the simplified formula method are systematically compared. The comparison results show that the SED calculated by the simplified formula in this paper is in good agreement with the finite element results. Referring to the traditional S-N evaluation curve, the W ¯ - N evaluation curve is proposed and verified. Through fatigue evaluation of a series of cruciform welding specimens, it is found that the result of fatigue strength evaluated by W ¯ - N with the simplified formula has a smaller scatter band.